Peningkatan Kualitas Produk dan Manajemen Usaha Jaket dan Tas Kulit Berbasis IT - Dwi Puryati; Hanifah Hanifah; Hery Haerudin (Universitas Serang Raya, 2017)
Garut city is famous for leather-based products such as jackets, bags, shoes and more. This devotional activity aims to help people who already have business to produce leather jackets and leather bags in the region of Garut, West Java in terms of improving product quality and simple IT-based bookkeeping. . The two partners in this service have the same problem (1) the length of time in producing jackets and bags and the lack of care of the risliting installation (2) does not understand the simple bookkeeping that SMEs should understand, (3) lacks a simple manual or book-based bookkeeping system IT, so it can not measure the financial performance of their business such as calculating profit, calculate inventory of goods or raw materials available, calculate the assets owned. The solutions offered are (1) procurement of cangklong machine tools along with application training, (2) simple bookkeeping training, and (3) procurement of simple IT-based bookkeeping systems and their implementation training. The monitoring activities are conducted in order to monitor the success rate of the planned activities in this service, while the evaluation activities are conducted with a view to seeing the sustainability of the program by business partners, such as whether or not equipment is used to accelerate the process of sewing jackets and leather bags and system implementation simple IT-based bookkeeping. . Keywords: product quality, bookkeeping system, IT